The Seducer's Diary - Kierkegaard, Soren, 1813-1855 (Book collections on Project MUSE., 2013)
""In the vast literature of love, The Seducer's Diary is an intricate curiosity--a feverishly intellectual attempt to reconstruct an erotic failure as a pedagogic success, a wound masked as a boast, "" observes John Updike in his foreword to Soren Kierkegaard's narrative. This work, a chapter from Kierkegaard's first major volume, Either/Or , springs from his relationship with his fiancee, Regine Olsen. Kierkegaard fell in love with the young woman, ten years his junior, proposed to her, but then broke off their engagement a year later. This event affected Kierkegaard profoundly.